PROTECTION OF FASHION DESIGN: A COMPARATIVE CASE STUDY BETWEEN INTELLECTUAL PROPERTY CODE (CODE DE LA PROPRIÉTÉ INTELLECTUELLE) AND UNITED STATES CODE TITLE 35 – PATENTS ACT - Tanyasri, Pornpirun (PEOPLE: International Journal of Social Sciences, 2021)
The purpose of this research is to study legal protection for fashion design in Thailand and a comparative Case Study between Intellectual Property Code (Code de la propriété intellectuelle) and the United States Code Title 35 – Patents Act. It is to say that fashion design is considered an industrial design that has been protected as a product design under the patent law and at the same time, it is considered as the work of applied art in accordance with Thai copyright law. The copyright law did not stipulate the explicit fashion design section but it only stipulated the listed protected work as the type of artistic works. Based on my study of fashion design protection in foreign countries, especially France, the law clearly states the protection for fashion design and listed protected works stipulating the type of protected works, and includes clear rules for what action constitutes the infringement. As a result of this strong protection of the law, innovation was created and progression for the fashion design industry was supported. In the United States of America, several ways of fashion design are protectable. Under the patent law, designers can apply for a design that qualifies as a new, unique and ornamental design and shall be eligible for protection under copyright law.